Breast cancer. Stage III: Utility of sistemic treatment - Viola Alles, Alberto; Vasallo, Alberto; Leibovici, Simón; Nunes, Elia; Mautone, Mariela (Cirugía del Uruguay, 1984)
In a group of 229 patients with breast cancer, 81 con• sult in stage 111; 32 were in the 111/A step and 49 in the 111/B. According to statistical analysis in wich survival was correlated with treatment were they local, regional or sistemic, we can conclude the utility of chemotherapy and hormonotherapy specially in 111/B stage. This results are explained by the metastatic potential that this group of patients has showed. This group benefits of this treatments